(untitled) (Medico Legal Update, 2021)
Acute myeloid leukemia is a malignant disease results from mutation in a multipotent haemopoietic stem cell. The study aimed to investigate NPM1 and FLT3-ITD mutations in Iraqi patients with AML and correlate results with other clinical and laboratory findings. Fifty-eight AML patients, admitted to Baghdad Teaching Hospital from October 2019 till March 2020 in addition to 25 normal controls, were included in the study. A detailed history, laboratory investigations including FLT3-ITD and NPM1 mutations were collected from and analyzed. FLT3-ITD was detected in 17.24% of patients, NPM1 mutation in 10.34%. Most of the patients are presented with pallor. FLT3-ITD mutation had a higher blast cell count (74%) while NPM1 mutation had higher WBCs count. Conclusion: AML is common in middle age group, patients with NPM1 mutation had significantly higher WBCs count while patients with FLT3-ITD mutation have higher blast percentage compared with nonmutated patients.